Bifunctional TiO2/AlZr thin films on steel substrate combining corrosion resistance and photocatalytic properties - Villardi de Oliveira, Caroline (2020)
A novel multi-functional bilayer coating combining an anti-corrosion Al-Zr (4 at.% Zr) underlayer and an anti-biofouling TiO2 top layer was deposited on high-speed steel (HSS) substrates. Al-Zr (4 at.% Zr) film, deposited by DC magnetron sputtering, which is a single phased supersaturated solid solution of Zr in Al, is used to provide sacrificial corrosion resistance of steels and TiO2 is added as a top layer to induce photocatalytic activity and hydrophilic behavior which can generate antifouling properties in order to slow down the biofouling process. The top TiO2 films, deposited at 550 °C by AACVD (aerosol-assisted chemical vapor deposition), consisting of anatase TiO2 microflowers physically attached to the TiO2 thin films present a high decomposition rate of Orange G dye (780 × 10-10 mol L-1·min-1). The enhanced photocatalytic performance is associated with the rough network and the presence of TiO2 microflowers capable of supporting the enhanced loading of organic contaminants onto the film surface. Electrochemical tests in saline solution have revealed that bilayer films provide cathodic protection for the steel substrate. The Al-Zr/TiO2 bilayer presents a lower corrosion current density of 4.01 × 10-7 A/cm2 and a corrosion potential of -0.61 V vs. Ag/AgCl, offering good protection through the preferential oxidation of the bilayer and an increased pitting resistance. The proposed functionalized coating combining anticorrosion and photocatalytic properties is a promising candidate for an anti-fouling system in sea water.